THE BEGINNING AND THE DURATION OF THE ONE-YEAR STATUTE OF LIMITATION IN THE OBLIGATION AND CONSUMER CONTEXT - Pilipović, Dejan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
This paper analyzes some issues related to the one-year statute of limitations, namely the beginning and duration of this period in the contract law and consumer law context. The focus is on reconsidering whether the length of the special one-year statute of limitations should be changed? In this context, is there chances for refinement and amendment of the provisions of the Contract and Tort Act, especially with regard to the beginning of this period, given that the law does not contain special rules on this in the one-year statute of limitations? The discussion is further complicated by the fact that in the Republika Srpska, the Consumer Protection Act contains a provision on a one-year statute of limitations for claims on services of general economic interest. Is the circle of claims or the rule on the beginning of this statute of limitations different from what the Contract and Tort Act prescribes? The aim of this paper is to find answers to these questions, using the methods of scientific research in the analysis of legislation, legal theory and case law, but also techniques - questionnaire (empirical research), which is of theoretical and practical importance.
Keywords: one year; statute of limitations; Contract and Tort Act; Consumer Protection Act; consumers